Unlocking Imagination: The Role of Literacy Programs in Inspiring Young Readers - Parinsi, Welimas Kristina; Musa, Kartika Septiary Pratiwi; Musa, Anugrah Dewi Lestasi (Malaqbi Publisher, 2024)
Schools play a vital role in supporting the learning process and fostering students' reading interest, especially through libraries. As information hubs, libraries provide a wide range of reading materials that help students expand their knowledge, think critically, and develop a deeper understanding of various concepts.Literacy is more than just reading and writing—it also includes comprehension, as well as the ability to analyze and use information in different contexts. Well-designed literacy programs can help students develop these skills, especially when combined with engaging reading activities. Students’ reading interest is a key factor in the success of literacy programs and can be nurtured through enjoyable activities with support from both families and schools. Additionally, collaboration among various stakeholders, including the government, educational institutions, and communities, is essential in creating a strong reading culture. With effective library management and collective efforts from all parties, literacy programs can positively impact educational quality and better prepare students for future challenges